Urbanisation from the margins: auto-construction of urban spaces for paratransit services in Kumasi, Ghana - Ibrahim Abu Abdulai; Sherif Issahaque; Lydia Faith Nsubuga (Urban, Planning and Transport Research)
In Ghana, paratransit services (three-wheeler taxis) have gained prominence because of their role in solving urban mobility challenges in major cities. While they are good at solving urban mobility challenges, they cause accidents and create congestion and inconveniences in the central business districts of cities. However, the literature on how paratransit service operators organise and create spaces for their operations is limited. We draw on peripheral urbanisation theory to understand how the operators produce urban spaces to conduct business in Kumasi. We hope to provide information for the planning and design of infrastructure that meets the needs of the different modes of urban mobility. In doing so, we adopt interviews and focus group discussions involving 35 purposively selected operators, 16 union executives, and two officials from the Kumasi Metropolitan Assembly to elicit the data. The responses were coded and categorised into themes for presentation. Findings indicate that the operators create space through negotiation and site selection. We conclude that securing spaces to conduct business is a major challenge to operators. Therefore, Kumasi Metropolitan Assembly should partner with communities, investors, and operators to create spaces for paratransit operators as it can provide a major source of revenue for development projects.